The gendering of musical instruments: what is it? Why does it matter to music therapy?. Issue 1 (1st January 2017) - Halstead, Jill; Rolvsjord, Randi
ABSTRACT: Musical instruments are a key material resource deeply imbedded in a broad range of practices in music therapy. The local uses of musical instruments in therapeutic contexts are influenced by, and interact with, the wider usage of musical instruments in music cultures as a whole. In such a cross-contextual field, musical instruments continue to be a site through which gender is affirmed and performed with many individuals drawn to particular instruments on the basis of their affordances in terms of gender and sexuality. In this article, we will focus on how issues of gender and sexuality can shape the use of musical instruments in contemporary musical practices with consideration of the implications for music therapy practice. Using the specific example of the electric guitar, we explore how issues of gender and sexual identity have become routinely associated with the instrument through personal and cultural narratives, discourse, instrument design and the performative practices of playing.